Kesesuaian Bidan Dalam Menerapkan Prosedur Pelayanan Persalinan Di PMB Pada Masa Pandemi Covid-19 - Zulfa, Siti Zakiah; Hidayat, Asri (Journal of Current Health Sciences, 2022)
During the Covid-19 pandemic, all health care facilities including PMB have tried to adjust delivery services to the Covid-19 health protocol. This study aimed to explore in depth the suitability of midwives in implementing delivery service procedures at PMB during the Covid-19 pandemic. The research method uses a qualitative descriptive study with a phenomenological approach. Data was collected using one on one in-depth online interviews with 10 informants using a semi-structured interview guide, then manual analysis using thematic analysis was carried out. The results of data analysis show that the use of masks, the application of hand hygiene, Covid-19 screening, and postnatal care education have been carried out by the Covid-19 health protocol. On the other side, the use of personal protective equipment, installation of delivery chambers, use of masks by patients, application of physical distancing, sampling of congenital hypothyroid screening, and self-isolation 14 days before delivery has not been fully implemented according to the Covid-19 health protocol. Intensive socialization and guidance through training activities for midwives in PMB related to delivery service guidelines during the Covid-19 pandemic are essential. Abstrak: Selama pandemi Covid-19, seluruh fasilitas pelayanan kesehatan termasuk PMB telah berupaya menyesuaikan pelayanan persalinan sesuai dengan protokol kesehatan Covid-19. Tujuan penelitian ini untuk menggali secara mendalam kesesuaian bidan dalam menerapkan prosedur pelayanan persalinan di PMB pada masa pandemi Covid-19. Metode penelitian menggunakan studi deskriptif kualitatif dengan pendekatan fenomenologi. Data dikumpulkan dengan cara one on one indepth interview online dengan 10 informan menggunakan panduan wawancara semi terstruktur, kemudian dilakukan analisis secara manual menggunakan analisis tematik. Hasil analisis data menunjukkan penggunaan masker, penerapan hand hygiene, screening Covid-19, serta edukasi perawatan pasca melahirkan telah dilaksanakan sesuai protokol kesehatan Covid-19. Disisi lain, penggunaan alat pelindung diri, pemasangan delivery chamber, penggunaan masker oleh pasien, penerapan physical distancing, pengambilan sampel skrining hipotiroid kongenital dan isolasi mandiri 14 hari sebelum persalinan belum sepenuhnya dilaksanakan sesuai protokol kesehatan Covid-19. Sosialisasi dan pembinaan secara intensif melalui kegiatan pelatihan kepada bidan di PMB terkait pedoman pelayanan persalinan pada masa pandemi Covid-19 sangat diperlukan.